Orientation dependent recovery and recrystallization behavior of hot-rolled molybdenum. (January 2015) - Primig, S.; Clemens, H.; Knabl, W.; Lorich, A.; Stickler, R.
Abstract: Due to its outstanding physical and chemical properties, technically pure molybdenum is nowadays frequently used in electronics and coating-technology besides its traditional applications as high temperature material. At present, the production of large plates which are used as sputtering targets is of great importance. These plates are processed by hot-rolling of sintered pre-material with intermediate recrystallization annealing treatments. In the present investigation we studied the microstructural and textural evolution during dynamic recovery and static recrystallization of molybdenum by using an industrially processed molybdenum plate which has been hot-rolled to a degree of deformation > 60% followed by static recrystallization annealing between 1000 and 1300 °C for various holding times up to 10 h. For the microstructural and textural characterization electron channeling contrast imaging and electron back-scatter diffraction were used. The orientation dependent subgrain size, the stored energy during hot-rolling, and the growth of individual subgrains upon static annealing indicated that the α-fiber subgrains, which are the largest ones after hot-rolling, exhibit slower static coarsening kinetics than the γ-fiber grains which are initially much smaller but contain a higher amount of stored energy. Furthermore, subgrains of other orientations located at in-grain shearbands seem to have growth advantages which cause a weakening of the rolling texture. A sluggish late-stage recrystallization behavior due to the recovery controlled annealing behavior has been revealed. Highlights: Static recrystallization behavior of hot-rolled molybdenum studied by ECCI and EBSD Orientation dependent subgrain coarsening was examined. Slower coarsening kinetics of α-fiber subgrains than γ-fiber subgrains Weakening of rolling texture due to growth advantages of subgrains at shearbands Sluggish late-stage recrystallization due to recovery controlled annealing behavior.